Strategy for Improving the Performance of the General Section of the Regional Secretariat - Baktiar Baktiar; Mujahid Mujahid; Syamsuddin Bidol (Journal La Bisecoman, 2023)
This research aims to identify and analyze strategies that can improve performance in the General Section of the North Penajam Paser Regency Regional Secretariat. This research was carried out in the regional secretary section of North Penajam Paser Regency, East Kalimantan Province in January-February 2024. With a qualitative approach, data collection techniques were through in-depth interviews and documentation studies. The main respondents included relevant officials, staff and managers in the General Section of the Regional Secretariat. The population in this study were all staff and managers who worked in the General Section of the Regional Secretariat of North Penajam Paser Regency. The main informants consist of relevant officials who have experience and knowledge relevant to performance improvement strategies in the General Department. Data analysis shows that there are several strategies that can improve performance in the General Department, including improving the administration system, increasing internal communication, developing employee skills, and implementing information technology. From the results of this research, it can be concluded that implementing these strategies can help increase efficiency and performance effectiveness in the General Section of the North Penajam Paser Regency Regional Secretariat. It is hoped that these findings can become a basis for related parties in developing better strategic steps to support more efficient and effective governance at the district level.